«Trust, but verify»: easier said than done (Epidemiology, Biostatistics, and Public Health, 2022)
Few weeks after the journal Science published a very unusual investigation by science journalist John Bohannon showing how many open access journals – among those asking for a submission or publication fee – don't really care about quality and accept for publication studies containing obvious and macroscopic mistakes, collecting money...